CT perfusion core and ASPECT score prediction of outcomes in DEFUSE 3. Issue 3 (April 2021) - Kim-Tenser, May; Mlynash, Michael; Lansberg, Maarten G; Tenser, Matthew; Bulic, Sebina; Jagadeesan, Bharathi; Christensen, Soren; Simpkins, Alexis; Albers, Gregory W; Marks, Michael P; Heit, Jeremy J
Background: The role of Alberta Stroke Program Early CT Score (ASPECTS) for thrombectomy patient selection and prognostication in late time windows is unknown. Aims: We compared baseline ASPECTS and core infarction determined by CT perfusion (CTP) as predictors of clinical outcome in the Endovascular Therapy Following Imaging Evaluation for Ischemic Stroke 3 (DEFUSE) 3 trial. Methods: We included all DEFUSE 3 patients with baseline non-contrast CT and CTP imaging. ASPECTS and core infarction were determined by the DEFUSE 3 core laboratory. Primary outcome was functional independence (modified Rankin Scale (mRS) ≤2). Secondary outcomes included ordinal mRS shift at 90 days and final core infarction volume. Results: Of the 142 patients, 85 patients (60%) had ASPECTS 8–10 and 57 (40%) had ASPECTS 5–7. Thirty-one patients (36%) with ASPECTS 8–10 and 11 patients (19%) with ASPECTS 5–7 were functionally independent at 90 days ( p  = 0.03). In the primary and secondary logistic regression analysis, there was no difference in ordinal mRS shift ( p  = 0.98) or functional independence (mRS ≤ 2; p  = 0.36) at 90 days between ASPECTS 8–10 and ASPECTS 5–7 patients. Similarly, primary and secondary logistic regression analyses found no difference in ordinal mRS shift ( p  = 1.0) or functional independence (mRS ≤ 2; p  = 0.87) at 90 days between patients with baseline small core ( < 50 ml) versus medium core (50–70 ml). Conclusions: Higher ASPECTS (8–10) correlated with functional independence at 90 days in the DEFUSE trial. ASPECTS and core infarction volume did not modify the thrombectomy treatment effect, which indicates that patients with a target mismatch profile on perfusion imaging should undergo thrombectomy regardless of ASPECTS or core infarction volume in late time windows.